HIV serostatus disclosure and associated factors among HIV positive pregnant women attending antenatal care services in northwest Ethiopia - Alemayehu, Daniel; Tadesse, Sebsibe; Adefris, Mulat; Birhanu, Zelalem (International Journal of Infection Control, 2014)
AbstractDisclosure of HIV serostatus by pregnant women to their sexual partners is critical for the successful prevention of mother to child transmission of HIV. This study examined the magnitude and factors associated with disclosure of HIV serostatus by pregnant women attending antenatal care services to their sexual partners in northwest Ethiopia.Institutional-based cross-sectional study design was employed from June to September 2013. All HIV positive pregnant women attending antenatal care follow up at government health facilities of Gondar, Bahir Dar and Metema town during the data collection period were included in the study. Data were collected by using pretested and structured interview questionnaire. Data analyses were done using SPSS for windows version 17.0. Multivariable analyses were applied to identify the relative effect of explanatory variables on the dependent variable.Out of the 263 HIV positive pregnant women participated in the study, 236 (89.7%) of them disclosed their HIV test result to their sexual partners. Knowing HIV serostatus of the sexual partner [AOR: 13.4, 95%CI: (2.6, 70.2)], knowing the importance of HIV serostatus disclosure [AOR: 10.3, 95%CI: (1.1, 98.7)] and being a rural resident [AOR: 0.2, 95%CI: (0.0, 1.0)] were the independent factors that determine HIV positive serostatus disclosure.This study showed that the magnitude of HIV serostatus disclosure by HIV positive pregnant women attending antenatal care services to their sexual partners was high. However, this doesn’t mean that there will be no need for further intervention activities as significant proportions of the study population still demonstrates nondisclosure. So, it is crucially important for HIV prevention programs to focus on factors, such as residence, increasing people’s awareness about HIV and ensuring smooth communication between sexual partners concerning HIV serostatus to address to problem.Keywords: Disclosure of HIV serostatus; HIV positive pregnant women; Sexual partner